A boronic acid-functionalized phthalocyanine with an aggregation-enhanced photodynamic effect for combating antibiotic-resistant bacteria. Issue 22 (22nd May 2020) - Lee, Eunhye; Li, Xingshu; Oh, Juwon; Kwon, Nahyun; Kim, Gyoungmi; Kim, Dongho; Yoon, Juyoung
Abstract : A boronic acid functionalized phthalocyanine displays aggregation-enhanced reactive oxygen species (ROS) generation and excellent photodynamic antibacterial activity. Abstract : Most existing photosensitizers ( e.g., porphyrins) are often aggregated in aqueous solution because of their large conjugated molecular structures. This aggregation usually results in a lack or low levels of reactive oxygen species (ROS) generation due to aggregation-caused quenching, which severely hampers the application of photosensitizers in photodynamic therapy (PDT). Herein, we make an interesting finding that a boronic acid-functionalized phthalocyanine (PcN4-BA) displays an uncommon phenomenon, an aggregation-enhanced photodynamic effect. The combination of the ability to form uniform nanostructured self-assemblies in water, highly efficient ROS generation and boronic acid-induced targeting give PcN4-BA excellent performances in antimicrobial PDT.